Looking South African: tracing the relationship between national pavilion and nation in South Africa s history at the Venice Biennale - Bronkowski, Annchen (Michaelis School of Fine Art, 2024)
The Venice Biennale, structured around national pavilions, is the world's oldest, largest and most prestigious biennial event for national art participation. South Africa has participated since 1950, and this has engendered thought-provoking, ever-changing debates about what constitutes artistic representation of national identity. This thesis presents the first institutional history of the South African national pavilion at the Venice Biennale. It highlights the organisational system of the pavilion, shaped by the South African Association of Arts in the twentieth century and the Department of Sports, Arts and Culture in the twenty-first, and analyses the politics of the pavilion's structural history. In so doing, it shows how certain sections and members of a community, who in some sense thought of themselves as ‘national' representatives, shaped the notion of a South African ‘national art' throughout the twentieth century. This study argues that the understanding of a ‘national' art has changed throughout the decades in South Africa. In the 1950s, the preoccupation was with stylistic issues and specifically with the shift from an academic to a modern art. Towards the 1960s, under the guidance of the New Group movement and artists like Walter Battiss, Alexis Preller, and Cecil Skotnes, South African art in Venice sought to capture a specific ‘South Africanness' rather than seeking to emulate modernism as it had developed in Europe and America. The country's exclusion from Venice during the boycott years of the 1970s to early 1990s coincided with the emergence of a politically-aware national aesthetic, while South Africa's re-entry to Venice in 1993 highlights a time when the tenets of post-apartheid nation-building had to be navigated within a postmodern, globalist art world focused on issues of post-nationalism. Finally, the thesis considers how contemporary concerns about inclusive representation have completely restructured South Africa's participation. This study shows that South Africa has always been caught, culturally, between national determinations and internationalist aspirations and that this tension is nowhere more sharply reflected than at the Venice Biennale.